2014
DOI: 10.21225/d59s3z
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Scaffolding and Interactive Learning Strategies in Online Courses for Working Nurses: Implications for Adult and Online Education

Abstract: This paper reviews the foundational literature of contemporary e-learning, with a focus on scaffolding, instructional design, and engagement. These concepts are then considered in two limited case studies, each involving e-learning and adult learners-in particular, nurse-learners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Course facilitators can consider participants’ previous experience with KT (e.g., beginner, intermediate, advanced) [ 46 ] and fit with participants’ previous learning and experience from other fields (e.g., terminology and concepts from physician education, project management, quality improvement, change management, behavior psychology etc.). Building upon previous knowledge can help scaffold and reinforce learning [ 34 , 47 ]. To help increase self-efficacy in KT, training initiatives can link to participants’ scope of practice (e.g., whether they are intervention developers, frontline implementers, or responsible for supporting front-line implementers) and opportunities to apply KT concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Course facilitators can consider participants’ previous experience with KT (e.g., beginner, intermediate, advanced) [ 46 ] and fit with participants’ previous learning and experience from other fields (e.g., terminology and concepts from physician education, project management, quality improvement, change management, behavior psychology etc.). Building upon previous knowledge can help scaffold and reinforce learning [ 34 , 47 ]. To help increase self-efficacy in KT, training initiatives can link to participants’ scope of practice (e.g., whether they are intervention developers, frontline implementers, or responsible for supporting front-line implementers) and opportunities to apply KT concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Monika (2013) noted that the evolving definition of e-learning describes e-learning as educational content or learning experiences that are provided or enabled by Internet technology to enhance an individual's knowledge and performance. As Salyers et al (2014) showed that e-learning, since its inception in the 1990s, has found its way into the public, private, and institutional sectors, and educational circles ranging from the K-12 sector to adult education. Moreover, its growth shows no signs.…”
Section: The Distance Education Conceptmentioning
confidence: 99%
“…It does not, however, refer to building course content; rather, it refers to building learning capacity through activities that support learning. As a practice, scaffolding can be used in face-toface, blended, and online learning settings (Salyers, Carter, Cairns, & Durrer, 2014).…”
Section: Scaffolding In An Intercultural Curriculummentioning
confidence: 99%